Cycle Tour Culture across Nepal Himalayas - Shrestha, Tara Lal (International Research Journal of MMC, 2025)
This study explores evolutionary process of cycle tour culture across Nepal Himalayas from the autoethnographic microhistorical approach with reference to the lived experiences of the pioneer Nepali cycle tour guides collected from July 2024 to January 2025 from 24 participants in the first-ever cycle tour guide training organized by Nepal Mountain Academy commenced in Central Campus, Tribhuvan University. It also includes (hi)story the first-ever cycle tour guide license distribution ceremony commenced at Tourism Office, Kathmandu on 29 December 2025. This study first investigates how foundation of adventure cycling in Nepal evolved opening avenues of possibilities through literature review, observation, interviews and discussions. Secondly, it connects the historical background of adventure cycling with cycle tour guide culture that evolved from a small community. It also explores how an informally evolved community generates historical momentum beyond boundary. In total 24 trainees - cycle tour guides - were participated in the training. This study was concentrated on the first cycle tour guide trainees in particular exploring their histories and stories. Most of them were well-trained high-altitude cycle tour operators/guides. Finally, it presents strategies and insights to operate cycle tour guide highlighting the resilience amidst precarity and policrisis while cycling in the high altitudes in Nepal. The findings highlight how a small history of cycle tour community of Nepal addresses higher level of socio-cultural and economic question of the nation. The conclusion offers avenues of the possibilities of cycle tour guide across Nepal.